New research strategies in retroperitoneal sarcoma. The case of TARPSWG, STRASS and RESAR: making progress through collaboration. Issue 4 (July 2019) - van Houdt, Winan J.; Raut, Chandrajit P.; Bonvalot, Sylvie; Swallow, Carol J.; Haas, Rick; Gronchi, Alessandro
Abstract : Purpose of review: Retroperitoneal sarcoma (RPS) is a rare disease, and until recently, its natural history and outcome were poorly understood. Recently, collaborations between individual centers have led to an unprecedented collection of retrospective and prospective data and successful recruitment to the first randomized trial as described here. Recent findings: A debate about the beneficial role of extended surgery in RPS triggered an initial collaboration between Europe and North America, the TransAtlantic RetroPeritoneal Sarcoma Working Group (TARPSWG). This collaboration has been instrumental in harmonizing the surgical approach among expert centers, characterizing the pattern of postresection failure of the different histological subtypes, identifying new ways to stage RPS and testing the role of preoperative radiotherapy in a randomized fashion (STRASS-1 study). The collaboration has now expanded to include centers from Asia, Australia and South America. A prospective registry has been started and a new randomized trial, STRASS-2, is in preparation to analyze the role of neoadjuvant chemotherapy for high-grade liposarcoma and leiomyosarcoma of the retroperitoneum. Summary: Collaboration is critical to study a rare disease like RPS. Both retrospective and prospective data are useful to improve knowledge, generate hypotheses and build evidence to test, whenever possible, in clinical trials.